Developing third-party purchase (3PP) services: New Zealand third-party logistics providers' perspectives. Issue 1 (9th January 2017) - Shi, Yangyan; Arthanari, Tiru; Wood, Lincoln
Abstract : Purpose: This paper aims to examine the opportunity for third-party logistics providers (3PLs) to develop further value-added services for their clients, focused on purchasing. The provider perspectives on third-party purchase (3PP) services are examined in conjunction with their business environment, with a survey informed by transaction cost economics. Design/methodology/approach: New Zealand 3PL providers were surveyed, and 166 responses were received. Structural equation modeling was used to test the conceptual model. Findings: From the perspective of 3PL providers, uncertainty, frequency and transaction size, but not asset specificity, are significantly associated with client value from a 3PP service. While asset specificity in investments is not required by 3PLs, they need a high frequency of orders, sufficient order size and low levels of uncertainty as supporting conditions for the development of 3PP services. Research limitations/implications: The sample focuses on 3PL providers and therefore does not address the behavioral characteristics of users or customers of the services. Originality/value: This study shows that 3PP services may be further developed by 3PL providers to improve the value offered to their clients.